2010
DOI: 10.1590/s0021-75572010000600014
|View full text |Cite
|
Sign up to set email alerts
|

Profilaxia para úlcera de estresse em pacientes internados em UTI pediátrica

Abstract: Objective: To assess use of stress ulcer prophylaxis in patients admitted to five pediatric intensive care units (PICUs) in Porto Alegre, Brazil.Methods: This was a multicenter, prospective, cross-sectional observational study. PICUs were visited on randomly defined days between April 2006 and February 2007, and the medical records of admitted patients were reviewed. Patients whose records had been previously assessed were excluded, as were those with upper gastrointestinal bleeding on admission. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
1
Order By: Relevance
“…Prescription of ranitidine or omeprazole is related to the stress ulcer prophylaxis protocol adopted by the PICU. In a prospective, cross-sectional, observational study in five PICUs in Porto Alegre, ranitidine was also the most commonly used drug for this prophylaxis (Araujo et al, 2010). National and international studies on adult critical care units indicated a variation of 44.3%-87.9% in the frequency of pDDIs observed (Hammes et al, 2008;Spriet et al, 2009;Reis and Cassiani, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Prescription of ranitidine or omeprazole is related to the stress ulcer prophylaxis protocol adopted by the PICU. In a prospective, cross-sectional, observational study in five PICUs in Porto Alegre, ranitidine was also the most commonly used drug for this prophylaxis (Araujo et al, 2010). National and international studies on adult critical care units indicated a variation of 44.3%-87.9% in the frequency of pDDIs observed (Hammes et al, 2008;Spriet et al, 2009;Reis and Cassiani, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of them, n=5 (3%) were performed by the clinical pharmacist. It is known that inappropriate use of drugs for stress ulcer prophylaxis and late changes in the administration route can be associated with potential adverse events, prolonged hospitalization times and higher costs, where a change in the administration route can effectively contribute to pharmacoeconomics and aim at ensuring that the medication will be administered via the recommended route 24,25 .…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Nous avons envoyé par courriel de l'information sur l'étude, dont un lien menant au sondage en dix points, à 111 répondants potentiels et deux rappels à ceux n'ayant pas répondu d'emblée. Nous avons évalué, au moyen d'un modèle de régression logistique, les points de vue des répondants à propos de la nécessité d'un essai et de leur participation potentielle à celui-ci en fonction de leurs caractéristiques individuelles et, à l'aide d'un test de 2 , les différences régionales.…”
Section: Résuméunclassified
“…1 In a prospective observational study of 398 children from 5 PICUs in Brazil, 78% received prophylaxis. 2 There is currently insufficient evidence to assess the benefits of routine prophylaxis. The 3 published trials that have reported macroscopic or important bleeding (340 children in total) [3][4][5] found no difference between children receiving prophylaxis and those receiving no prophylaxis (relative risk 0.71, 95% confidence interval [CI] 0.42-1.19, p = 0.19).…”
Section: Introductionmentioning
confidence: 99%